The Effects of Acid Activation on the Thermal Properties of Polyvinylpyrrolidone and Organoclay Composites - F. Kooli (Journal of Chemistry)
The thermal stabilities of polyvinylpyrrolidone-organoclays or organo-acid-activated clay composites prepared by chemical exchange reactions were assessed. The raw clay mineral was acid-activated prior to expansion by cetyltrimethylammonium surfactants. The acid activation process affected the intercalated amount of cetyltrimethylammonium cations in the resulting organoclays and, thus, the amount of polyvinylpyrrolidone in the composite. The content of cetyltrimethylammonium cations decreased with the extent of acid activation. The organophilic modification of the clay mineral was an important step in the intercalation of the polyvinylpyrrolidone molecules and, thus, in the expansion of the silicate sheets from 3.80 nm to 4.20 nm. The composites exhibited better crystalline order with intense reflections at lower angles. The thermal stability of organoclays, acid-activated clays, and composites was studied using thermogravimetric analysis and in situ X-ray diffraction. The decomposition of intercalated surfactants occurred at lower temperatures relative to the neat surfactant salt, and the basal spacing of the organoclays (or acid-activated clays) shrunk to 2.0 nm at 215°C. However, the basal spacing of composites exhibited better stability and collapsed to 2.0 nm at 300°C. This type of material could offer an alternative stable product for engineering purposes in the design of new composites.